A rationale for universal tranexamic acid in major joint arthroplasty: overall efficacy and impact of risk factors for transfusion. Issue 1 (1st November 2018) - Pavenski, Katerina; Ward, Sarah E.; Hare, Gregory M.T.; Freedman, John; Pulendrarajah, Robisa; Pirani, Razak A.; Sheppard, Nicholas; Vance, Colm; White, Alexander; Lo, Nick; Waddell, James P.; Ho, Alex; et al.
Abstract : BACKGROUND: Tranexamic acid (TXA) therapy is effective in reducing postoperative red blood cell (RBC) transfusion in total joint arthroplasty (TJA), yet uncertainty persists regarding comparative efficacy and safety among specific patient subgroups. We assessed the impact of a universal TXA protocol on RBC transfusion, postoperative hemoglobin (Hb), and adverse outcomes to determine whether TXA is safe and effective in TJA, both overall and in clinically relevant subgroups. STUDY DESIGN AND METHODS: A retrospective observational study was performed on patients undergoing TJA at our institution spanning 1 year before and after the implementation of a universal protocol to administer intravenous (IV) TXA. The primary outcome was percentage of patients transfused, and secondary outcomes were perioperative Hb and occurrence of adverse events (death, myocardial infarction, stroke, seizure, pulmonary embolism, deep vein thrombosis, and acute kidney injury ). Outcomes were compared in pre‐ and post‐protocol groups with χ 2 analysis. Logistic regression compared risk of transfusion in pre‐ and post‐protocol subgroups of patients with differing risk for transfusion (anemia, body mass index [BMI], and sex). RESULTS: No differences were found in baseline patient characteristics across pre‐ and post‐protocol groups (n = 1084 and 912, respectively). TXA use increased from 32.3% to 92.2% while transfusion rates decreased from 10.3% to 4.8% (p < 0.001). Postoperative Day 3 Hb increased from 95.8 to 101.4 g/L (p < 0.001). Logistic regression demonstrated reduced transfusion in post‐protocol subgroups regardless of sex, anemia, or BMI (p < 0.001). No increase in adverse events was observed (p = 0.8451). CONCLUSIONS: Universal TXA was associated with a reduction of RBC transfusion, overall and in clinically relevant subgroups, strengthening the rationale for universal therapy.